INDIVIDUAL PSYCHOLOGY OF NOAH CALHOUM IN THE NOTEBOOK A NOVEL WRITTEN BY NICHOLAS SPARKS (ANALYSIS OF THE MAIN CHARACTER) - Podungge, Rusni; Umar, Irmawaty; Dauhi, Irmawati (Reduplikasi: Jurnal Penelitian Pendidikan Bahasa Indonesia, 2022)
This study analyzes the main character components of individual psychology in The Notebook. This research focuses on examine Noah Colhum as a main character in novel The Notebook by Nicholas Sparks. The main theory of this study is Individual psychology by Alfred Adler. The novel was written by Nicholas Sparks. This study provides six component of individual psychology, such as Inferiority, superiority, style of life, social interest, creative self and fictional final goal .This study use descriptive qualitative analysis. As a result, Noah as a main character has all components of Individual Psychology which emphasizes people struggles to be a better self. Penelitian ini menganalisis komponen psikologi pada karakter utama dalam Â Novel The Notebook. Penelitian ini berfokus untuk mengkaji Noah Colhum sebagai tokoh utama dalam novel The Notebook karya Nicholas Sparks. Teori utama dari penelitian ini adalah Psikologi individu oleh Alfred Adler. Novel ini ditulis oleh Nicholas Sparks. Studi ini memberikan enam komponen psikologi individu, seperti Inferioritas, superioritas, gaya hidup, minat sosial, diri kreatif dan tujuan akhir fiksi. Penelitian ini menggunakan analisis deskriptif kualitatif. Akibatnya, Noah sebagai tokoh utama memiliki semua komponen Psikologi Individu yang menekankan perjuangan orang untuk menjadi diri yang lebih baik.